2019
DOI: 10.1155/2019/3038103
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chromium(VI) onto Freshwater Snail Shell-Derived Biosorbent from Aqueous Solutions: Equilibrium, Kinetics, and Thermodynamics

Abstract: In this study, freshwater snail shells (FSSs) containing CaCO3 were used as a low-cost biosorbent for removing Cr(VI) from aqueous solutions. The characteristics of FSS and mechanism of Cr(VI) adsorption onto FSS were investigated. The FSS biosorbent was characterized using nitrogen adsorption/desorption isotherm, X-ray diffraction, scanning electron microscopy with energy dispersive spectroscopy, and Fourier transform infrared spectroscopy. The adsorption mechanism was determined by conducting various batch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…In comparison, the samples after adsorption by metal ions showed traced amount of corresponding Cu(II) and Zn(II) being adsorbed, as summarized in Table 2 . The EDX results were in good agreement with related studies reported elsewhere [ 13 , 36 ]. The elemental mapping results of the UVS samples before and after adsorption is presented in Figure 4 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison, the samples after adsorption by metal ions showed traced amount of corresponding Cu(II) and Zn(II) being adsorbed, as summarized in Table 2 . The EDX results were in good agreement with related studies reported elsewhere [ 13 , 36 ]. The elemental mapping results of the UVS samples before and after adsorption is presented in Figure 4 .…”
Section: Resultssupporting
confidence: 92%
“…The results revealed the morphology of the UVS featuring the laminar structure with some degree of surface roughness due to the deposited materials. The morphological characteristics (e.g., surface structure) of the UVS were similar to those of the absorbent shells reported in the other studies [ 36 , 37 , 38 ]. The dispersed tubular holes were also observed on the UVS surface.…”
Section: Resultssupporting
confidence: 83%
“…The stretched band at 1150 cm −1 is related to the stretching of the COO-anion, at 1080 cm −1 to the symmetric and asymmetric stretching of the C-O group of the ester vibration and at 1030 cm −1 to the functional group C-O-C [3]. The presence of hydroxyl groups, carbonyl groups, ethers and aromatic compounds is due to the high content of cellulose and lignin in the biomaterial; it is evidence of the lignocellulosic structure of the biomaterial under study, which contributes to the metal ion adsorption process [33].…”
Section: Totalsmentioning
confidence: 98%
“…Activated carbon is a commercial and frequently used adsorbent; however, it is of high cost [14,[20][21][22]. Recently, biosorbents derived from various kinds of biomass such as green coconut shell, clay, fly ash, sugarcane bagasse, mango kernel, coffee, and rice husk have been applied in many studies regarding the removal of various pollutants from an aqueous solution [23]. Biosorbents have been modified by various methods to enhance the adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%